Decay resistance of thermally modified Eucalyptus grandis wood against wild strains of Trametes versicolor and Pycnoporus sanguineus. Issue 6 (2nd November 2022) - Cantera, Leandro; Alonso, Raquel; Lupo, Sandra; Bettucci, Lina; Amilivia, Agostina; Martínez, Jorge; Dieste, Andrés
ABSTRACT: Eucalyptus grandis presents low durability, and due to its anatomical characteristics, impregnation with chemicals is not an effective alternative to increase it. This work analyses the effect that thermal modification carried out in an oxygen depleted atmosphere has on mass, density, hygroscopicity, chemical composition of the cell wall and decay resistance against locally collected wild strains of wood destroying Basidiomycetes, Trametes versicolor and Pycnoporus sanguineus . E. grandis boards were modified in a vacuum environment ( P  = –100 kPa) at 160°C, 180°C and 200°C for 1, 2 and 3 h. Hygroscopicity was determined by a sorption isotherm over saturated saline solutions at 25°C. The cell wall composition was characterized by the content of structural carbohydrates, lignin and total extractives. A mini-block fungal test was performed by exposing treated wood samples to mycelia, using Populus sp. as reference. The results showed that the thermal treatment caused mass and density reduction. Modified samples showed a reduction in xylose content while lignin content increased, and cellulose content remained constant. Treated samples presented lower hygroscopicity, especially the ones modified at higher temperatures. The analysis by the Hailwood-Horrobin model showed that the main effect occurred at the monomolecular level, causing a reduction of the sorption capacity of the treated wood. The fungi test evidenced that the modification increased the decay resistance of E. grandis against T. versicolor and P. sanguineus . Both fungi were capable of degrading modified wood, but had limited activity, explained by a reduction of moisture content and a change in the chemical composition of the wood.